Age-related macular degeneration: a perspective on genetic studies. - Patel, N; Adewoyin, T; Chong, N (2008)
AIM: Age-related macular degeneration (AMD) is a common macular disease in the developed world and recent studies have shown that specific genes may be associated with it and may contribute to a higher risk of developing AMD. OBJECTIVE: Our objective was to review systematically recent publications related to the genetics of AMD and provide relevant information that would help both scientists and clinicians in advising patients. METHOD: A systematic search was performed on PubMed, Medline, and National Library of Medicine as well as ARVO abstracts using key words relevant to the genetic associations of AMD. RESULTS: The most important genetic associations in AMD involved the complement factor H (CFH) gene, which showed that possession of the variant Y402H polymorphism significantly increases the risk for AMD. Protective genes have also been identified such as those on either factor B (BFor complement factor B (CFB)) or complement component 2 (C2) genes. The genes involved in inherited macular dystrophies such as ATP-binding cassette, subfamily A (ABC1), member 4 (ABCA4), vitelliform macular dystrophy (VMD2), tissue inhibitor of matrix metalloproteinase-3 (TIMP3), and EFEMP1have yielded some important information but further confirmatory work has yet to establish a clear association with AMD. CONCLUSION: Patients with AMD possess specific genetic variants of the CFHgene, which put them at a higher risk of developing the disease. Other unaffected individuals may possess certain protective genetic variants, which could prevent them from developing AMD. Further research will no doubt shed light on other such mechanisms and these will be useful in identifying possible direct targets for drugs or indirectly through modulation of the genes responsible for disease presentation.